Performance of protected concrete against chemically aggressive environments - Aguiar, J. L. Barroso de (2007)
Three different types of surface protections were tested: silicone hydrophobic agent, acrylic and epoxy coatings. Surface treatments act as a barrier between the environment and the concrete, preventing or retarding the entry of harmful substances and cutting off the transportation path into concrete. There is a linear relation between the ionic permeability of the resin and the electrolytic conductivity of the resin. Virtually all the surface protecions are permeable to water, enough to be little effective controlling the corrosion but not the ionic permeability which is much lower. It seems to be a connection between the permeability and the characteristics of the density of the crosslinking of the coating. The water (or aggressive solution) is transported trough the film in a process with several phases called permeation, which depends on two independent parameters: the solubility of the water in the polymer and its diffusivity or ability to pass trough the film, both concerning the molecular structure of the resin. The effectiveness of a surface protection preventing the permeation depends on how close and strongly connected are the resin molecules. This work intends to contribute to a better understanding of the performance of protected concrete in chemically aggressive environments, by presenting results of ion diffusion and resistance to aggressive solutions of several hydrophobic agents and coatings used to protect concrete. The results indicate that the overall performance of epoxy resin was better than that of other types of protections.